Peran Pemerintah Daerah dalam Pengembangan Pertanian Organik (Studi pada Dinas Pertanian dan Kehutanan Kota Batu) - Mohammad Nor Habibi (Jurnal Administrasi Publik, 2015)
Abstract: The Role of Local Government in The Development of Organic Farming. (Case Studies inÂ  department of Agriculture and Forestry Batu). Organic agriculture is an alternative solution in order to deal with the challenge of globalization and also to cope with the trend in the demand of consumer and world market that begin to concern with products that must be free from chemical residue, be environmental friendly and be health friendly. The objective of this research is to understand, to describe and to analyze the role of local government through the Office of Agriculture and Forestry of Batu City for Organic Farming development in Batu City. The author is interested to acknowledge the role of local government in Organic Farming development. Research type is qualitative with descriptive approach. Analysis method is Miles and Huberman. Based on the result of analysis, the role of local government in Organic Farming development is already good and effective because it has implemented socialization, education and facilitation of the program. From these three indicators of program, several outcomes are obtained concerning with organic area, land width, chemical pesticide reduction, number of farmers and plant species. The constraining factors include: (a) limited human resource with skill, (b) the reducing quality and quantity of natural resources, and (c) excessive land use conversion. Keywords: Role, Local Government, Organic Farming. Abstrak: Peran Pemerintah Daerah dalam Pengembangan Pertanian Organik (Studi pada Dinas Pertanian dan Kehutanan Kota Batu). Pertanian organik di anggap sebagai alternative solusi dalam menghadapi tantangan globalisasi dan trend permintaan konsumen maupun pasar dunia yang berkembang saat ini yang mulai sangat peduli terhadap produk â€“ produk bebas residu kimia, ramah lingkungan dan menyehatkan. Penelitian ini bertujuan untuk mengetahui, mendiskripsikan dan menganalisis bagaimana peran pemerintah daerah melalui Dinas Pertanian dan Kehutanan Kota Batu dalam pengembangan pertanian organik di Kota Batu, Berdasarkan hasil penelitian yang telah dilakukan, Peran Pemerindah daerah dalam pengembangan pertanian organik sudah berjalan dengan baik dan efektif dalam menjalankan pelaksanaan program sosialisasi, edukasi, dan fasilitasi dan dari hasil 3 (tiga) indikator tersebut membuahkan hasil seperti kawasan organik, luas lahan dan pengurangan pestisida kimia, jumlah petani dan jenis tanaman, meskipun dalam pelaksanaannya masih ada faktor penghambat, yaitu a) Keterbatasan SDM yang mempunyai kemampuan, b) kualitas dan kuantitas SDA yang semakin menurun, c) alih fungsi lahan. Kata kunci : Peran, Pemerintah Daerah, Pertanian Organik.